Simulations to Teach Science Subjects: Connections Among Students’ Engagement, Self-Confidence, Satisfaction, and Learning Styles - Almasri, Firas (Education and information technologies, 2022)
With the increasing technology integration practices in education, the adoption of computer simulations to teach conceptual understanding of science concepts is widely accepted by educators across the globe. To understand the connections between learners’ engagement and satisfaction with simulations for science learning and their learning styles, the present study analyzed 1034 university students' perceptions and experiences of using simulations for learning physics, chemistry, and biology subjects. The study took place in a large public university in a gulf country. Precisely, this study provides an empirically driven exploration of the connection between tertiary students' engagement and satisfaction with simulation-based learning and their learning styles. The findings of this study showed that the participants showed a very high level of engagement and satisfaction with the use of simulations for learning science concepts in the subjects of physics, chemistry, and biology. Their self-confidence and VAK learning styles, particularly the kinesthetic style, were significant predictors of their engagement and satisfaction with the learning process. The findings from this study have implications for the benefit of researchers and practitioners interested in the effective adoption of computer simulations as a pedagogical approach in science education.